(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In the education system, training highly qualified personnel with practical skills that meet the requirements of the labor market is a pressing task. In this regard, special attention is being paid in Uzbekistan to integrating the educational process with production. The dual education model serves to deepen cooperation between education and industry, develop students’ professional competence, ensure the rapid adaptation of graduates to the labor market, and effectively implement innovative technologies. Dual education is financed in cooperation with commercial organizations and government institutions within professional and higher education institutions. The research is aimed at analyzing the scientific foundations, practical significance, and implementation mechanisms of the dual education system, and highlights the role of this model in improving education quality and the efficiency of personnel training. In addition, the article provides an in-depth overview of the dual education systems of developed countries.